Homogeneous Catalytic Kinetics of Methyl Glycolate Hydrolysis. Issue 5 (4th March 2016) - Xu, Yan; Meh, Ablikim; Yang, Guangcun; Zhao, Yujun; Chen, Qu; Li, Zhenhua; Ma, Xinbin
Abstract: Catalytic hydrolysis of methyl glycolate is a promising way to produce glycolic acid with high purity. The hydrolysis of methyl glycolate was investigated both in a stirred‐batch reactor and in a reactive distillation column. Batch hydrolysis distillation was found to be rather effective in improving the conversion of methyl glycolate. A mechanism model including the cooperative catalysis of sulfuric acid and the generated glycolic acid was developed based on the acid‐catalyzed hydrolysis mechanism and the protolysis equilibrium; then, the model was further simplified according to the relationship between the concentrations of hydroxonium ions and their providers. This simplified model could be easily introduced to Aspen Plus and applied to simulating the homogeneous hydrolysis process of methyl glycolate with or without sulfuric acid as catalyst via the reactive distillation technique. Abstract : The autocatalysis effect plays an important role in the hydrolysis of methyl glycolate with a small amount of sulfuric acid. Based on the acid‐catalyzed hydrolysis mechanism and the protolysis equilibrium, a kinetic model including the cooperative catalysis of sulfuric acid and autocatalysis was proposed, which well predicts the performance of methyl glycolate hydrolysis in a reactive column.